RELIGIOUS LIFE IN CHINUA ACHEBE’S NOVEL THINGS FALL APART - Habibi Habibi; M. Manugeren; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2022)
This research is aimed at reflecting how Chinua Achebe reveals the religious life of Igbo people before and after the coming of the missionaries as well as the invasion of British in the southeastern part of Nigeria during the late 19th century. Achebe reflects that various practices of social and religious life are thrilling, cruel and even inhumane. This research is considered significant and worthy since it is an exertion to understand historical knowledge and life lessons about religious life of the local people. This study is supported by the theory of literary sociology proposed by Laurenseon and Swingewood's to understand and evaluate literary works by considering social aspects and holistically conducted by descriptive qualitative method in which the data from the novel are analyzed to reveal the religious life of Igbo people before and after the coming of British people and the significant contributions as well as changes they have brought. The findings of this research designates that various inhumane religious and cultural practices, such as abandoning or throwing twins born into the evil forest, throwing people dying with diseases, mutilating babies who die at birth and considering ogbanje, not burying people who die by suicide, surely no longer happen in Igbo society. In short, the changes in religious life carried out by white people bring enlightenment and positive life changes for Igbo people.